ASIVA (AKU SIAP VAKSIN) AS AN EFFORT TO IMPROVE COMMUNITY KNOWLEDGE AND READINESS TO RECEIVE THE COVID-19 VACCINATION - Yurike Septianingrum; Lono Wijayanti; Sulistyorini Sulistyorini (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Information that is not true or commonly called a